2013
DOI: 10.1002/anie.201309217
|View full text |Cite
|
Sign up to set email alerts
|

Full Functionalization of the Imidazole Scaffold by Selective Metalation and Sulfoxide/Magnesium Exchange

Abstract: A simple, flexible, and straightforward method for the functionalization of all the positions of the imidazole heterocycle through regioselective arylations, allylations, acylations, and additions to aldehydes is disclosed. Starting from the readily available key imidazole 1, highly functionalized imidazole derivatives have been synthesized in a regioselective manner from directed metalations and a sulfoxide/magnesium exchange. Moreover, the selective N3-alkylation followed by deprotection of N1 (trans-N-alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 56 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…Thus subjection of 3 pa to Meerwein reagent resulted in the formation of imidazolium product 11 , and the following cleavage of the pyrimidyl group gave rise to the N‐methylated imidazole 12 . Similar strategy has been reported by using N‐sulfamoyl protected imidazoles as the starting materials ,…”
Section: Resultsmentioning
confidence: 97%
“…Thus subjection of 3 pa to Meerwein reagent resulted in the formation of imidazolium product 11 , and the following cleavage of the pyrimidyl group gave rise to the N‐methylated imidazole 12 . Similar strategy has been reported by using N‐sulfamoyl protected imidazoles as the starting materials ,…”
Section: Resultsmentioning
confidence: 97%
“…Several general strategies can be envisioned for the preparation of the polysubstituted imidazoles, either through the intermediacy of α–substituted ketones ( 12 → 11 ), hydroamination of alkynes 10b, 16 or through the functionalization of pre-formed imidazoles ( 13 → 11 ). 17 In each case, the strategies are executed to avoid introducing the polar 2-amino substituent until the end of the synthetic sequence. In this context we pursued the latter approach, relying on halogen-Grignard exchange reactions of 4,5-diiodoimidazole derivatives and subsequent electrophilic quench.…”
Section: Resultsmentioning
confidence: 99%
“…While this was encouraging, this meant that an exchange of imidazole N-substituents was necessary and that this had to be accomplished in a position selective manner. Fortunately, Robiette, 30 Sames 31 and more recently Knochel 17b have demonstrated that the DMAS-protecting group can be removed with a methyl group via the intermediacy of an imidazolium salt formed by reaction with methyl triflate or Meerwein’s salt. Given this encouraging precedent, the corresponding DMAS-protected 4,5-diiodoimidazole was used as a starting material.…”
Section: Resultsmentioning
confidence: 99%
“…A sulfoxide–magnesium exchange and a second Negishi cross‐coupling leads to the 3,4‐diarylated pyridine 56 in 61 % yield (Scheme 8). The sulfoxide–magnesium exchange is used to fully functionalize the imidazole skeleton [33] . Furthermore, the sulfoxide–magnesium exchange allows the efficient generation of aziridinylmagnesium derivatives that can be further functionalized by a Negishi cross‐coupling [34] .…”
Section: The Halogen–metal Exchangementioning
confidence: 99%